Plasticity in the human central nervous system - Cooke, S. F.; Bliss, T. V. P. (Brain (London, England : 1878), 2006)
Long-term potentiation (LTP) is a well-characterized form of synaptic plasticity that fulfils many of the criteria for a neural correlate of memory. LTP has been studied in a variety of animal models and, in rodents in particular, there is now a strong body of evidence demonstrating common underlying molecular mechanisms in LTP and memory. Results are beginning to emerge from studies of neural plasticity in humans. This review will summarize findings demonstrating that synaptic LTP can be induced in human CNS tissue and that rodent and human LTP probably share similar molecular mechanisms. We will also discuss the application of non-invasive stimulation techniques to awake human subjects to induce LTP-like long-lasting changes in localized neural activity. These techniques have potential therapeutic application in manipulating neural plasticity to treat a variety of conditions, including depression, Parkinson's disease, epilepsy and neuropathic pain.